Unraveling Shade Tolerance and Plasticity of Semi-Evergreen Oaks: Insights From Maritime Forest Live Oak Restoration - Thyroff, Emily C.; Burney, Owen T.; Mickelbart, Michael V.; Jacobs, Douglass F. (Frontiers in Plant Science, 2019)
Oaks (Quercus spp.) are generally intermediate in shade tolerance, yet there is large variation within the genus in shade tolerance and plasticity in response to varying resource availability. Ecophysiological knowledge specific to semi-evergreen Quercus spp. from sub-temperate maritime forests is lacking relative to temperate deciduous oaks. We studied the influence of light availability and plant competition on leaf physiology and performance of semi-evergreen Q. virginiana on a barrier island along the US southern Atlantic coast. Seedlings were underplanted in pine (Pinus taeda) plantation stands with varying overstory density (clearcut, heavy thin, light thin, and no thin; creating a gradient of understory light availability) and vegetation (no competition removal or herbaceous competition removal) treatments. After two years, seedling survival was higher with increasing light availability (clearcut = heavy thin > light thin > no thin). Seedling growth (i.e., diameter, height, and crown width) increased similarly with increasing thinning intensity, while vegetation control was mainly beneficial to seedling growth in clearcuts. These responses were explained by foliar nitrogen and leaf trait measurements, which followed the same pattern. Q. virginiana seedlings demonstrated high plasticity in their ability to acclimate to varying resource availability, as indicated by light response curves, specific leaf area, stomatal density, stomatal pore index, and maximum theoretical stomatal conductance. Light compensation and saturation points illustrated seedling capacity to increase net CO2 assimilation with increased light availability. Leaves on trees in the high light environment had the highest net CO2 assimilation, stomatal density, stomatal pore index, maximum theoretical stomatal conductance and lowest specific leaf area. Although we demonstrated the relative shade tolerance of Q. virginiana in lower light environments (i.e., heavy and light thin plots), this semi-evergreen species shows high plasticity in capacity to respond to varying resource availability, similar to some other Quercus spp. from mesic and Mediterranean environments.